2008
DOI: 10.1007/s00330-008-1009-7
|View full text |Cite
|
Sign up to set email alerts
|

Multi-contrast, isotropic, single-slab 3D MR imaging in multiple sclerosis

Abstract: To describe signal and contrast properties of an isotropic, single-slab 3D dataset [double inversion-recovery (DIR), fluid-attenuated inversion recovery (FLAIR), T2, and T1-weighted magnetization prepared rapid acquisition gradient-echo (MPRAGE)] and to evaluate its performance in detecting multiple sclerosis (MS) brain lesions compared to 2D T2-weighted spin-echo (T2SE). All single-slab 3D sequences and 2D-T2SE were acquired in 16 MS patients and 9 age-matched healthy controls. Lesions were scored independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
89
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 28 publications
10
89
0
Order By: Relevance
“…3 D sequences have the advantage of good signal and contrast properties despite the small voxels. High SNRs and CNRs have been described for 3 D FLAIR sequences [17,18]. These findings are confirmed by our measurements, which showed higher values for all calculated ratios except for the CNR lesion GM.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…3 D sequences have the advantage of good signal and contrast properties despite the small voxels. High SNRs and CNRs have been described for 3 D FLAIR sequences [17,18]. These findings are confirmed by our measurements, which showed higher values for all calculated ratios except for the CNR lesion GM.…”
supporting
confidence: 91%
“…Analyzing the Cube images, only four lesions were described as mixed gray/white matter (one in the 2 D FLAIR) and none was located clearly intracortically. Again a definite conclusion cannot be drawn from this small study, yet these findings are in accordance with the results of Moraal et al who found significantly lower numbers of intracortical lesions with a 3 D FLAIR sequence than with a 3 D double inversion recovery (DIR) sequence [17,18]. It may well be possible that Cube FLAIR improves detection of supratentorial white matter lesions while different sequences are necessary for optimized imaging of the infratentorial and cortical regions.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…For 3D-FLAIR, there are many reports regarding application to multiple sclerosis. 5,6,[42][43][44][45][46][47][48][49][50][51][52][53][54] Smaller lesions can be detected by 3D-FLAIR than by 2D-FLAIR due to thinner slices and fewer flow artifacts with 3D-FLAIR. 45,46 Excellent detection of cortical lesions by 3D-FLAIR has also been reported (Fig.…”
Section: Clinical Applicationsmentioning
confidence: 99%